EFFECTS OF ATORVASTATIN ON ENDOTHELIAL DYSFUNCTION IN TYPE 2 DIABETIC PATIENTS WITH DIFFERENT DURATION F THE DISEASE - G. A. Batrak; S. E. Miasoedova; O. I. Kelesh (Столичная издательская компания, 2015)
Aim. To evaluate dynamics of endothelial vasoregulatory function in type 2 diabetic patients after 6 months of combined treatment with atorvastastin 20 mg/day depending on the disease duration and target lipid levels achievement.Material and methods. The total of 161 type 2 diabetic patients with dyslipidemia were enrolled into non-randomized open-label study, of which 149 patients were assigned to a group of follow-up (group 1) and 12 to a group of comparison (group 2). All the patients received combined antihypertensive and glucose-lowering therapy. Patients of group 1 were additionally receiving atorvastatin 20 mg/day. Parameters of glucose and lipid metabolism and reactive hyperemia test were assessed in all patients initially and 6 months later.Results. Patients with newly diagnosed diabetes were more likely to restore endothelial vasoregulatory function as compared to the patients with 1-5 and 6-10 years of diabetes duration (56% vs 42% and 35%, respectively). Patients who reached target lipid levels as compared with those who didn't, more often revealed normalization of endothelial function (38% vs 33%, respectively). Atorvastatin benefited was more effective in newly diagnosed diabetic patients who had achieved target lipid levels.Conclusion. Addition of atorvastatin to glucose-lowering and antihypertensive treatment can restore endothelial vasoregulatory function in 6 months in more than half of new-onset type 2 diabetic patients. Maximal effect of combined therapy with atorvastatin is obtained at early stages of diabetes mellitus and at target lipid levels achievement.